KOMITE AUDIT, RETURN ON ASSETS, AND UKURAN PERUSAHAAN SEBAGAI PENENTU CASH HOLDINGS PERUSAHAAN - Veronica Veren Milenia; Kusuma Indawati Halim (POLITEKNIK LP3I JAKARTA, 2026)
This study investigates the determinants of corporate cash holdings among transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This study uses a quantitative approach using secondary data obtained from the annual reports and financial statements of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. A purposive sampling technique was employed to select 20 companies, resulting in 100 firm-year observations. The data were analyzed using multiple linear regression after passing normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that ROA has a positive and significant effect on cash holdings, indicating that more profitable companies tend to accumulate larger cash reserves to ensure financial flexibility and self-financing capacity. Firm size also exhibits a positive and significant relationship, indicating that larger companies, due to their operational complexity and higher capital requirements, maintain higher levels of liquidity. Conversely, audit committees exhibit an insignificant effect, suggesting that governance structure plays a supporting, rather than direct, role in determining corporate cash holding policies in this sector.